Plasmonic toroidal excitation with engineering metamaterials - Wu, Pin Chieh (2019)
Natural toroidal molecules, such as biomolecules and proteins, possess toroidal dipole moments that are hard to be detected, which leads to extensive studies of artificial toroidal materials. Recently, toroidal metamaterials have been widely investigated to enhance toroidal dipole moments while the other multipoles are eliminated due to the spacial symmetry. In this talk, we will show several cases on the plasmonic toroidal excitation by engineering the near-field coupling between metamaterials, including their promising applications. In addition, a novel design for a toroidal metamaterial with engineering anapole mode will also be discussed.